Christian Origins and the Establishment of the Early Jesus Movement. - Stanley E. Porter; Andrew W. Pitts (Editors) (Texts and Editions for New Testament Study, 2018)
Christian Origins and the Establishment of the Early Jesus Movement explores the events, people, and writings surrounding the founding of the early Jesus movement in the mid to late first century. The essays are divided into four parts, focused upon the movement's formation, the production of its early Gospels, description of the Jesus movement itself, and the Jewish mission and its literature. This collection of essays includes chapters by a global cast of scholars from a variety of methodological and critical viewpoints, and continues the important Early Christianity in its Hellenistic Context series.